Economic and social progress in Latin America : 1988 report - Inter-American Development Bank.; David Rockefeller Center for Latin American Studies (Washington, D.C. : Inter-American Development Bank, 1988)
This book is on the report on economic and social progress in Latin America.
Includes bibliographical references.
oo 21/01/2019
Loans
Keywords: Economic history; Economic growth; Social conditions; Science ad technology; Latin America